A left-to-right bias in number-space mapping across ages and cultures - Elena Eccher; Mathilde Josserand; Serge Caparos; Esther Boissin; Marco Buiatti; Manuela Piazza; Giorgio Vallortigara (Nature Communications)
Abstract Number and space are inherently related. Previous research has provided evidence that numbers are aligned to a so-called “mental number line”, which is malleable and affected by cultural factors mostly linked to literacy-related habits. However, preverbal humans and non-human animals also map numerosities into space, in a consistent left-to-right direction. These contrasting findings raise the question of whether Spatial Numerical Associations (SNA) are culturally or biologically determined. Here, we investigated Italian adults, Italian preschoolers, and Himba adults (an indigenous population with an oral cultural system) to examine whether cultural influences are necessary for SNA to emerge. We found that, when explicitly asked to order numerosities, only Italian adults showed a consistent left-to-right preference, while preschoolers and Himba adults did not have a consistent preference for one direction or the other. On the other hand, in a numerosity comparison task, all groups performed better when small numerosities were presented in the left hemispace. These results suggest that humans may display two forms of SNAs, one that emerges mostly in implicit tasks and is biologically determined, and one that emerges in explicit ordering tasks and is determined by cultural habits.